Impaired SARS-CoV-2 specific T-cell response in patients with severe COVID-19 - Rümke, Lidewij W.; Smit, Wouter L.; Bossink, Ailko; Limonard, Gijs J. M.; Muilwijk, Danya; Haas, Lenneke E. M.; Reusken, Chantal; van der Wal, Sanne; Thio, Bing J.; van Os, Yvonne M. G.; Gremmels, Hendrik; Beekman, Jeffrey M.; et al. (Frontiers in Immunology, 2023)
Cellular immune responses are of pivotal importance to understand SARS-CoV-2 pathogenicity. Using an enzyme-linked immunosorbent spot (ELISpot) interferon-γ release assay with wild-type spike, membrane and nucleocapsid peptide pools, we longitudinally characterized functional SARS-CoV-2 specific T-cell responses in a cohort of patients with mild, moderate and severe COVID-19. All patients were included before emergence of the Omicron (B.1.1.529) variant. Our most important finding was an impaired development of early IFN-y-secreting virus-specific T-cells in severe patients compared to patients with moderate disease, indicating that absence of virus-specific cellular responses in the acute phase may act as a prognostic factor for severe disease. Remarkably, in addition to reactivity against the spike protein, a substantial proportion of the SARS-CoV-2 specific T-cell response was directed against the conserved membrane protein. This may be relevant for diagnostics and vaccine design, especially considering new variants with heavily mutated spike proteins. Our data further strengthen the hypothesis that dysregulated adaptive immunity plays a central role in COVID-19 immunopathogenesis.